Implementation of participatory organizational change in long term care to improve safety. (September 2021) - Van Eerd, Dwayne; D'Elia, Teresa; Ferron, Era Mae; Robson, Lynda; Amick, Benjamin
Highlights: Long Term Care facilities are fast-paced and physically demanding environments. This study assessed the implementation of a participatory organizational program. Participants described positive program implementation impacts and culture changes. A participatory program can be implemented in LTC to address MSD hazards. Abstract: Introduction: Long Term Care (LTC) facilities are fast-paced, demanding environments placing workers at significant risk for injuries. Health and safety interventions to address hazards in LTC are challenging to implement. The study assessed a participatory organizational change intervention implementation and impacts. Methods: This was a mixed methods implementation study with a concurrent control, conducted from 2017 to 2019 in four non-profit LTC facilities in Ontario, Canada. Study participants were managers and frontline staff. Intervention sites implemented a participatory organizational change program, control sites distributed one-page health and safety pamphlets. Program impact data were collected via Survey (self-efficacy, control over work, pain and general health) and observation (Quick Exposure Checklist). Interviews/focus groups were used to collect program implementation data. Results: Participants described program impacts (hazard controls through equipment purchase/modification, practice changes, and education/training) and positive changes in culture, communication and collaboration. There was a statistically significant difference in manager self-efficacy for musculoskeletal disorder (MSD) hazards between the control and intervention sites over time but no other statistical differences were found. Key program implementation challenges included LTC hazards, staff shortage/turnover, safety culture, staff time to participate, and communication. Facilitators included frontline staff involvement during implementation, management support, focusing on a single unit, training, and involving an external program facilitator. Conclusion: A participatory program can have positive impacts on identifying and reducing MSD hazards. Key to success is involving frontline staff in identifying hazards and creating solutions and management encouragement on a unit working together. High turnover rates, staffing shortages, and time constraints were barriers as they are for all organizational change efforts in LTC. The implementation findings are likely applicable in any jurisdiction. Practical Application: Implementing a participatory organizational change program to reduce MSD hazards is feasible in LTC and can improve communication and aid in identification and control of hazards.